Peran Akun Media Sosial Berbasis Konten Pariwisata Pada Pengambilan Keputusan Wisatawan untuk Mengunjungi Destinasi Wisata Pada Era Digital - Nasution, Olivia Barcelona; Rohman, Isnanda Zainur (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 02, Januari 2022, 2022)
Word of mouth evolved by the development of the internet. Besides offline word of mouth, online word of mouth, especially social media, is also on the rise. This study aims to examine the effect of online and offline word of mouth on the perceived destination image and the effect of the perceived image on the decision to visit a tourist destination. The number of respondents in this study were 148 people who were selected by purposive sampling technique. Hypothesis testing in this study uses multiple and simple linear regression using IBM SPSS 22 software. The results of this study are online and offline word of mouth have a positive effect on the perceived destination image and the perceived image also has a positive effect on tourists' decisions to visit tourist destinations. Keywords: eWOM, WOM, perceived destination image, visit decision, tourist destination.